2021
DOI: 10.3390/cancers13071713
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer and Immunity: From the Wet Lab to Individuals

Abstract: Immunotherapy is a very promising field of research and application for treating cancers, in particular for those that are resistant to chemotherapeutics. Immunotherapy aims at enhancing immune cell activation to increase tumor cells recognition and killing. However, some specific cancer types, such as colorectal cancer (CRC), are less responsive than others to the current immunotherapies. Intrinsic resistance can be mediated by the development of an immuno-suppressive environment in CRC. The mutational status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 170 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…The cancer cells may undergo transitions to enhance their motility and extravasate to colonize at distant locations 1 , 18 . Prior studies have demonstrated the existence of phenotypically different subpopulations of tumorigenic and non-tumorigenic cells in various human malignancies, including acute myeloid leukaemia 19 , 20 , chronic myeloid leukaemia 21 , 22 , breast cancer 23 , 24 , glioblastoma 25 , 26 , colorectal cancer 27 , 28 , pancreatic cancer 29 , 30 , and ovarian cancers 23 , 31 . Recent investigations revealed the presence of multiple heterogenic cancer cells, such as Epithelial to mesenchymal transition (EMTs) 32 , 33 , Mesenchymal to epithelial transitions (METs) 18 , 34 , Circulating tumor cells (CTCs) 24 , 35 , Disseminated Tumor Cells (DTCs) 36 , 37 , etc., in many cancer progression and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…The cancer cells may undergo transitions to enhance their motility and extravasate to colonize at distant locations 1 , 18 . Prior studies have demonstrated the existence of phenotypically different subpopulations of tumorigenic and non-tumorigenic cells in various human malignancies, including acute myeloid leukaemia 19 , 20 , chronic myeloid leukaemia 21 , 22 , breast cancer 23 , 24 , glioblastoma 25 , 26 , colorectal cancer 27 , 28 , pancreatic cancer 29 , 30 , and ovarian cancers 23 , 31 . Recent investigations revealed the presence of multiple heterogenic cancer cells, such as Epithelial to mesenchymal transition (EMTs) 32 , 33 , Mesenchymal to epithelial transitions (METs) 18 , 34 , Circulating tumor cells (CTCs) 24 , 35 , Disseminated Tumor Cells (DTCs) 36 , 37 , etc., in many cancer progression and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Intratumor heterogeneity and inter-tumor heterogeneity, among other molecular, phenotypic, and functional characteristics, can obstruct diagnosis and pose therapeutic challenges in bone, lung, brain, and liver cancer metastasis, these reports suggest that there is currently no systematic and comprehensive assessment of the molecular makeup of metastases 7 . Few reports have demonstrated the existence of phenotypically different subpopulations of tumorigenic and non-tumorigenic cells in various human malignancies, including acute myeloid leukaemia 8,9 , chronic myeloid leukaemia 10,11 , breast cancer 12,13 , glioblastoma 14,15 , colorectal cancer 16,17 , pancreatic cancer 18,19 , and ovarian cancers 12,20 .…”
Section: Introductionmentioning
confidence: 99%